2015
DOI: 10.1016/j.ydbio.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cultures of trophoblast stem cells autonomously develop vascular-like spaces lined by trophoblast giant cells

Abstract: The maternal blood space in the mouse placenta is lined not by endothelial cells but rather by various subtypes of trophoblast giant cells (TGCs), defined by their location and different patterns of gene expression. While TGCs invade the spiral arteries to displace the maternal endothelium, the rest of the vascular space is created de novo but the mechanisms are not well understood. We cultured mouse trophoblast stem (TS) cells in suspension and found that they readily form spheroids (trophospheres). Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…These endeavours will involve optimising the culture conditions for known placental stem and progenitor cells and deriving novel self-renewing trophoblast progenitor sub-populations. This could be accomplished by establishing placental organoids that rely on intrinsic signals driving self-organisation coupled to self-renewal (Rai and Cross, 2015). This strategy has proved to be successful for a number of mouse and human organoid systems (Huch and Koo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These endeavours will involve optimising the culture conditions for known placental stem and progenitor cells and deriving novel self-renewing trophoblast progenitor sub-populations. This could be accomplished by establishing placental organoids that rely on intrinsic signals driving self-organisation coupled to self-renewal (Rai and Cross, 2015). This strategy has proved to be successful for a number of mouse and human organoid systems (Huch and Koo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…). Recent work using a three‐dimensional culture system has shown that trophoblast stem cells differentiate into a variety of TGC subtypes, and create microcavities lined by TGCs that express a variety of markers (Rai and Cross, ); it will be of interest to investigate the expression of p57 kip2 during their differentiation in such a system.…”
Section: Discussionmentioning
confidence: 99%
“…3D culture of so-called "trophospheres" is a new technique used to form differentiated trophectodermal cells from TS cell aggregates (Rai and Cross, 2015), and is described as being more reproducible than simple monolayer differentiation. This technique results in cavitated structures lined by parietal TGCs which surround maternal blood sinuses in the placenta; such forced and defined differentiation may make interpretation of endocytosis assays more robust, and could be applied to our TS cells.…”
Section: Chapter 7 Discussionmentioning
confidence: 99%
“…taken from Rai and Cross, 2015 This method was attempted for our TS clones, using hanging drops to culture TSCs. After trypsinisation, drops (30-50µl) of~500 TSCs were placed in a non-adhesive culture dish, then hung upside down to culture.…”
Section: Figure 7-1: Formation Of Trophospheres By Tsc Aggregates (A)mentioning
confidence: 99%